Applications of nanoscience in photomedicine - Hamblin, Michael R.; Avci, Pinar (Woodhead Publishing series in biomedicine ;, 2015)
Nanoscience has become one of the key growth areas in recent years. It can be integrated into imaging and therapy to increase the potential for novel applications in the field of photomedicine. In the past commercial applications of nanoscience have been limited to materials science research only, however, in recent years nanoparticles are rapidly being incorporated into industrial and consumer products. This is mainly due to the expansion of biomedical related research and the burgeoning field of nanomedicine. Applications of Nanoscience in Photomedicine covers a wide range of nanomaterials including nanoparticles used for drug delivery and other emerging fields such as optofluidics, imaging and SERS diagnostics. Introductory chapters are followed by a section largely concerned with imaging, and finally a section on nanoscience-enabled therapeutics.